High Purity Isolation of Low Density Neutrophils Casts Doubt on Their Exceptionality in Health and Disease - Hardisty, Gareth R.; Llanwarne, Frances; Minns, Danielle; Gillan, Jonathan L.; Davidson, Donald J.; Gwyer Findlay, Emily; Gray, Robert D. (Frontiers in Immunology, 2021)
Low density neutrophils (LDNs) are described in a number of inflammatory conditions, cancers and infections and associated with immunopathology, and a mechanistic role in disease. The role of LDNs at homeostasis in healthy individuals has not been investigated. We have developed an isolation protocol that generates high purity LDNs from healthy donors. Healthy LDNs were identical to healthy normal density neutrophils (NDNs), aside from reduced neutrophil extracellular trap formation. CD66b, CD16, CD15, CD10, CD54, CD62L, CXCR2, CD47 and CD11b were expressed at equivalent levels in healthy LDNs and NDNs and underwent apoptosis and ROS production interchangeably. Healthy LDNs had no differential effect on CD4+ or CD8+ T cell proliferation or IFNγ production compared with NDNs. LDNs were generated from healthy NDNs in vitro by activation with TNF, LPS or fMLF, suggesting a mechanism of LDN generation in disease however, we show neutrophilia in people with Cystic Fibrosis (CF) was not due to increased LDNs. LDNs are present in the neutrophil pool at homeostasis and have limited functional differences to NDNs. We conclude that increased LDN numbers in disease reflect the specific pathology or inflammatory environment and that neutrophil density alone is inadequate to classify discrete functional populations of neutrophils.